2000
DOI: 10.1603/0022-2585-37.5.784
|View full text |Cite
|
Sign up to set email alerts
|

Oral Infection of <I>Culicoides sonorensis</I> (Diptera: Ceratopogonidae) by Vesicular Stomatitis Virus

Abstract: Vesicular stomatitis virus serotype New Jersey (VSNJV) was mixed with bovine blood or fetal bovine serum (FBS) and fed across silicone membranes to laboratory populations of Culicoides sonorensis Wirth & Jones. In an initial study, virus was detected after 13 d in 21% of the midges that received an FBS/VSNJV mixture. In subsequent time-course experiments, engorged females were collected and maintained at 20.0 degrees C and assayed for VSNJV immediately after feeding and at 1, 3, 7, 10 and 13 d after feeding. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…In addition, colonized biting midges, Culicoides sonorensis Wirth & Jones, are susceptible to VSNJV infection (Nunamaker et al 2000, Drolet et al 2005, and experimentally infected midges have been shown to transmit the virus to guinea pigs ) and cattle .…”
mentioning
confidence: 99%
“…In addition, colonized biting midges, Culicoides sonorensis Wirth & Jones, are susceptible to VSNJV infection (Nunamaker et al 2000, Drolet et al 2005, and experimentally infected midges have been shown to transmit the virus to guinea pigs ) and cattle .…”
mentioning
confidence: 99%
“…Recently, these epizootics have been more frequent for unknown reasons. While the natural transmission cycle of VS viruses is currently unclear, laboratory studies (Cupp et al 1992, Mead et al 2000, Nunamaker et al 2000 have demonstrated arthropod transmission of VS viruses, and epidemiological studies have strongly associated exposure to arthropods with clinical cases (Francy et al 1988;Corn et al 1990). …”
mentioning
confidence: 99%
“…It is possible that in nature, VSV exploits both hematophagous and herbivorous vector transmission mechanisms. VSV has been shown to replicate in a variety of hematophagous insects (2,3,9,11,17), as well as in two nonhematophagous insects: leafhoppers (7) and grasshoppers (10). Although most of these insects do not travel distances great enough to explain the typical pattern of VSV spread to new and distant areas during outbreaks, the migratory grasshopper M. sanguinipes is an exception.…”
Section: Discussionmentioning
confidence: 99%